Prevalence of depression and its associated factors among patients with confirmed COVID-19 in Makkah, Saudi Arabia - Alqurashi, Eid; Aldobyany, Ahmad; Touman, Abdelfattah; Alqahtani, Abdullah; Alsaggaf, Rajaa; Alnashiwaaty, Omar; Ghaleb, Nabil; Mabar, Hanan; Albanna, Amr S. (Frontiers in Psychiatry, 2022)
Background In early December 2019, a cluster of acute pneumonia of viral etiology had been identified in Wuhan, China. Later on, it has been named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing a worldwide pandemic. This pandemic triggered unprecedented health-related psychiatric sequalae. We aim in this study to evaluate the prevalence of depression and its associated factors among confirmed patients with COVID-19. Methodology This is a cross-sectional study, we included adult patients more than 18 years old who have been diagnosed with PCR-confirmed COVID-19 and managed in a hospital, home, or hotel. A self-administered online questionnaire based on Patient Health Questionnaire (PHQ-9) Quick Depression Assessment questionnaire was used. Results A total of 143 subjects completed the PHQ-9 questionnaire. The prevalence of moderate to severe depression was 34%. Prevalence of depression was positively associated with the female gender (p-value = 0.013). Location of COVID-19 management and financial status did not affect the prevalence of depression. Conclusion The prevalence of depression among patients with COVID-19 is high, which underscores the importance of active screening and management of depression in this population.